Comprehensive prediction model of drilling temperature of UD-CFRP laminates considering the combined action of main cutting edge and chisel edge. (1st June 2023) - Li, Shujian; Teng, Hanwei; Dai, Longyu; Zhou, Yongchao; Li, Changping; Li, Pengnan; Ko, Tae Jo
Highlights: A comprehensive prediction model of drilling temperature of UD-CFRP is proposed. The combined action of chisel edge and main cutting edge is considered in the model. Predicted drilling temperature agree well with experimental results. The temperature distribution during UD-CFRP drilling is analyzed. The effects of fiber orientation angle and machining parameters are revealed. Abstract: The accuracy of predicting drilling temperature in CFRP drilling is helpful to process optimization and defect suppression. The previous models for predicting CFRP drilling temperature are few and need to be more systematic. Combined with theoretical modeling and experimental verification, a comprehensive theoretical model is developed to predict the temperature distribution during the drilling process of unidirectional CFRP (UD-CFRP), which considers the synergy of the chisel edge and main cutting edge of the drill bit, as well as the influence of fiber orientation angle (FOA). Results show that the predicted peak temperatures parallel to and vertical to the fiber direction present tiny errors of 2.26–5.27% and 4.44–7.55% respectively, indicating that the model is reliable. At 1 mm from the hole wall of UD-CFRP, the peak temperature decreases with the increase of FOA. The drilling temperature decreases with the increase of feed rate and increases with the increase of spindle speed. At the outlet layer of UD-CFRP, the contribution of spindle speed to temperature rise is more significant than the feed rate.